2022
DOI: 10.1111/gcb.16327
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor on “Satellite observations document trends consistent with a boreal biome shift”

Abstract: Berner and Goetz (2022) reported the results of a study of changes in vegetation greenness using 30 m pixel Landsat satellite imagery comprising a total of 90 km 2 across a circumboreal 8.4 million km 2 . Prior to analyses, the authors removed a total of 6.7 million km 2 (44.4% of the 15.1 million km 2 study region) by masking out unvegetated, human footprint, and recently disturbed areas. The authors determined annual maximum vegetation greenness at each pixel from 1985 to 2019 and tested for trends in greeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In this region, we find a mix of greening, no change, and sporadic browning from 2000 to 2019 (Figure 1). We agree with Timoney (2022) that a biome shift is “unlikely to be uniform in magnitude, or even sign” in this region or others, which is a point we made in several places throughout the paper. Ultimately, we maintain our conclusion that “there have been systematic trends in vegetation greenness during recent decades that are consistent with an emerging boreal biome shift associated with ongoing climate warming.”…”
Section: Figuresupporting
confidence: 87%
See 2 more Smart Citations
“…In this region, we find a mix of greening, no change, and sporadic browning from 2000 to 2019 (Figure 1). We agree with Timoney (2022) that a biome shift is “unlikely to be uniform in magnitude, or even sign” in this region or others, which is a point we made in several places throughout the paper. Ultimately, we maintain our conclusion that “there have been systematic trends in vegetation greenness during recent decades that are consistent with an emerging boreal biome shift associated with ongoing climate warming.”…”
Section: Figuresupporting
confidence: 87%
“…In his Letter to the Editor, Timoney (2022) suggests that Berner and Goetz's (2022) remote sensing assessment of an emerging boreal forest biome shift is “problematic” due to the sample size, exclusion of recently burned areas, and lack of ground validation data, as well as inconsistent with a recent study focused on western and central Canada (Timoney & Mamet, 2020). Here, we address these concerns.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Berner and Goetz (2022), based on analysis of normalized difference vegetation index (NDVI) data, concluded that greening in recent decades is linked to climate warming increasing growth, biomass, and probably recruitment of trees and shrubs in a significant portion of the forest-tundra ecotone, but such changes have not occurred everywhere along the cold margins of the boreal forest. Timoney (2022) observed that Berner and Goetz sampled only 0.001% of their circumpolar study region; that deletion of recently-burned areas biased the results towards greening; that ecologically meaningful interpretation of NDVI data requires ground-based vegetation data; that relevant studies that found no evidence for a biome shift were not cited; and that absence of a systematic directional change in greenness meant that it was premature to conclude that a boreal biome shift was underway. Timoney (2022) concluded that ‘to understand and predict ecosystem change we need more ground-truth.…”
Section: Introductionmentioning
confidence: 99%
“…Timoney (2022) observed that Berner and Goetz sampled only 0.001% of their circumpolar study region; that deletion of recently-burned areas biased the results towards greening; that ecologically meaningful interpretation of NDVI data requires ground-based vegetation data; that relevant studies that found no evidence for a biome shift were not cited; and that absence of a systematic directional change in greenness meant that it was premature to conclude that a boreal biome shift was underway. Timoney (2022) concluded that ‘to understand and predict ecosystem change we need more ground-truth. Without ground-truth, we have only speculation.’…”
Section: Introductionmentioning
confidence: 99%